Shoot the Arrow, Then Paint the Target: CEO Compensation and Institutional Shareholder Services Benchmarking - Iyer, Subramanian R.; Palmon, Oded; Sankaran, Harikumar (Journal of Financial and Quantitative Analysis, 2023)
We document that firms that expect their CEOs’ compensation to exceed the median CEO compensation of their Institutional Shareholder Services (ISS) peers influence ISS to revise these peer sets. Controlling for changes in firm characteristics that ISS uses to select peers, we find that ISS applies an abnormally high turnover rate in the members of these peer sets and increases the representation of focal firms’ chosen peers. This turnover results in increases in the medians of the ISS peers’ CEO compensation and size. We find that these firms underperform and conclude that they attempt to camouflage high CEO pay to mitigate outrage costs.